Study of Urinary Alpha Glutathione-S-Transferase in Children with Idiopathic Nephrotic Syndrome (Journal of Renal and Hepatic Disorders, 2020)
Glomerulopathy associated with recurrent or persistent proteinuria may lead to progressive tubulointerstitial fibrosis. Early detection of tubulointerstitial fibrosis may result in a more favorable outcome of chronic kidney disease (CKD) because nephroprotective treatment may be instituted in due course. One of the early markers of tubulointerstitial fibrosis is glutathione S-transferase (GST). The aim of this study was to determine urinary alpha-GST in children with idiopathic nephrotic syndrome (INS), either in remission or relapse. This case–control study included 40 children with primary nephrotic syndrome (NS), either in remission or relapse. Also, 40 healthy children, age- and sex-matched as controls, were selected from the outpatients and the pediatric nephrology unit of Al-Zahraa Hospital, Al-Azhar University. Urinary alpha-GST was investigated in the study groups on the same lines as that of routine investigations of INS. Children with INS have significantly higher urinary GST either in remission or relapse, it was (5.23 ± 1.90) ng/mL, (5.32 ± 1.52) ng/mL respectively compared with healthy controls, it was (2.59 ± 1.12) ng/mL with (P = 0.001). A positive correlation between urinary alpha-GST and body weight BW, height, body mass index (BMI), white blood cells (WBCs) count, erythrocyte sedimentation rate, serum (cholesterol, triglyceride [TG]) level, blood urea nitrogen (BUN), and duration of the disease. Urinary alpha-GST was increased in children with NS even after remission, and it consequently led to oxidative stress and tubulointerstitial fibrosis. Nephroprotective treatment is recommended even in cases with INS, either in remission or relapse.
Keywords: children; nephrotic syndrome; urinary alpha-GST